2019
DOI: 10.1002/ece3.5216
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and interspecific associations among trees at different stand development stages in the natural secondary forests on the Loess Plateau, China

Abstract: Quercus wutaishansea populations on the Loess Plateau are currently becoming more dominant in natural secondary forests, whereas Pinus tabulaeformis is declining. In the present paper, the diameter class (instead of age) was used to classify the different growth stages as juvenile, subadult, or adult, and the univariate function g(r) was used to analyze the dynamic changes in spatial patterns and interspecific associations in three 1‐ha tree permanent plots on the Loess Plateau, NW China. Our results suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Previous spatial analytical methods have described the scattering of individual trees and the spatial distribution of tree size, whereas our newly proposed spatial analysis methods use new quantitative and vectorial marks to determine the driving factors that led to the spatial patterns. That is, traditional methods only analyze unmarked and quantitatively marked patterns such as a significant segregated distribution of certain species adults and a significant clustered distribution of subadults and juveniles at extreme small scales (Nguyen et al 2014;Gu et al 2019), a wide clustered distribution of some typical species at small scales (Nguyen et al 2016), or a significantly smaller tree size of a minor species around the dominant species (Wiegand and Moloney 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous spatial analytical methods have described the scattering of individual trees and the spatial distribution of tree size, whereas our newly proposed spatial analysis methods use new quantitative and vectorial marks to determine the driving factors that led to the spatial patterns. That is, traditional methods only analyze unmarked and quantitatively marked patterns such as a significant segregated distribution of certain species adults and a significant clustered distribution of subadults and juveniles at extreme small scales (Nguyen et al 2014;Gu et al 2019), a wide clustered distribution of some typical species at small scales (Nguyen et al 2016), or a significantly smaller tree size of a minor species around the dominant species (Wiegand and Moloney 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Information on species associations provides a theoretical basis for enrichment planting [51]. Additionally, the light requirement of tree species are also an important factor in species arrangement for enrichment planting [74,75]. Generally, tree species are grouped into shade-intolerant species, shade-tolerant species, and opportunistic species according to their light requirements [76,77].…”
Section: Implications For Enrichment Plantingmentioning
confidence: 99%
“…The spatial patterns and associations of tree species would change with different growth stages of tree species ( Gu et al, 2019 ; Ledo, 2015 ; Zhou et al, 2019 ). Studies found that most species tended to be aggregated at seedling stage, while they tended to be regular or random at adult stage ( Condit et al, 2000 ; Getzin et al, 2006 ; Stoll & Bergius, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, secondary forests have become a major forest type in many regions worldwide ( Brown & Lugo, 1990 ; Finegan, 1996 ); they account for 70% of the natural forests in northeastern China ( Yang et al, 2010 ). Research on spatial patterns and associations of tree species at different developmental stages may be informative in understanding the structure and dynamic processes of secondary forests ( Gu et al, 2019 ). In this study, we analyzed spatial patterns and associations of tree species at different developmental stages (seedling, sapling and adult) in a montane secondary forest of eastern Liaoning Province, China.…”
Section: Introductionmentioning
confidence: 99%